Perú: the path to a pluralistic society - Emil Dabagyan (Ибероамериканские тетради, 2017)
This article is focused on the particularities of the Peruvian political development after the failure of A. Fujimori. His name embodies the consolidation of economy and slide toward authoritarianism which resulted in the acute crisis and the collapse of the regime. Subsequently, Perú started advancing along the democratic paradigm assuming the regular changes in power of political leaders regardless their ideological preferences according to the universally recognized norms and principles